Classics of Pedagogical Science on the Principles of Natural Conformity as an Integral Part of Society - Saidov Bakhtiyar Muhammadievich (International Journal on Integrated Education, 2022)
The article deals with natural conformity as one of the leading principles of pedagogy, which is included in all pedagogical theories, is explicitly or covertly present in all textbooks on pedagogy, and is recognized as the main teacher-practitioner by all scientific teachers. This is explained by the fact that the principle of conformity to nature in the theory of pedagogy came from the depths of folk experience in education.